2019
DOI: 10.3390/cells9010092
|View full text |Cite
|
Sign up to set email alerts
|

The Meniscus Tear: A Review of Stem Cell Therapies

Abstract: Meniscal injuries have posed a challenging problem for many years, especially considering that historically the meniscus was considered to be a structure with no important role in the knee joint. This led to earlier treatments aiming at the removal of the entire structure in a procedure known as a meniscectomy. However, with the current understanding of the function and roles of the meniscus, meniscectomy has been identified to accelerate joint degradation significantly and is no longer a preferred treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 109 publications
(122 reference statements)
0
63
0
Order By: Relevance
“…We expected a high concentration of VEGF in the vascular-rich tissues such as muscle and bone, however, interestingly we noted a high level in the meniscus tissue, while that in muscle was low. The meniscus has been described to have heterogeneous structure, and possesses a vascularity only in its middle and outer zones (Mauck and Burdick, 2015;Jacob et al, 2019). Porcine menisci has also been described to have increased VEGF content from the inner to the outer zone, explaining why the meniscus tissue expressed a high VEGF concentration (Di Giancamillo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We expected a high concentration of VEGF in the vascular-rich tissues such as muscle and bone, however, interestingly we noted a high level in the meniscus tissue, while that in muscle was low. The meniscus has been described to have heterogeneous structure, and possesses a vascularity only in its middle and outer zones (Mauck and Burdick, 2015;Jacob et al, 2019). Porcine menisci has also been described to have increased VEGF content from the inner to the outer zone, explaining why the meniscus tissue expressed a high VEGF concentration (Di Giancamillo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm if different tissue-derived soluble ECMs elicited tissue-specific cellular responses, we analyzed their bioactivities by seeding hSMSCs in high density in a 3D collagen gel. As far as the regeneration of musculoskeletal tissues are concerned, SMSCs possess the potential to differentiate into multiple lineages (Fan et al, 2009;Dai et al, 2015;Jacob et al, 2019). Moreover, hSMSCs have already been applied in previous clinical studies in the tissue engineering field (Shimomura et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review article on stem cell therapies on meniscus repair, Jacob et al 19 concluded that mesenchymal stem cells appear to be safe and effective in producing superior-quality meniscal repairs. However, presently there is no consensus on the ideal cell source and scaffold for meniscus regeneration.…”
Section: See Related Article On Page 932mentioning
confidence: 99%
“…Jacob et al summarize the pre-clinical and clinical studies using MSCs and tissue engineering for meniscal repair and regeneration. Available literature demonstrates that MSCs appear to be safe and effective in meniscal repairs [ 40 ].…”
Section: Stem Cell-based Therapymentioning
confidence: 99%
“…This Special Issue includes both research [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] and reviews articles [ 10 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] which cover wide ranges of stem cell research: adult stem cells, cancer stem cells, pluripotent stem cells, and complex 3D organoid/cell aggregate models [ 26 , 27 , 33 ], with the focuses on stem cell biology/technology [ 10 , 23 , 24 , 25 , 26 , 31 , 32 , 34 ], and stem cell-based disease modeling [ 10 , 27 , 29 , 31 , 33 , 38 , 43 ] and cell therapy [ 24 , 28 , 30 , 32 , 35 , 36 , 37 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%